A longitudinal study on the association between facets of mindfulness and eating disorder symptoms in individuals diagnosed with eating disorders. (22nd November 2018) - Sala, Margarita; Vanzhula, Irina A.; Levinson, Cheri A.
Abstract: Mindfulness‐based treatments for eating disorders could be improved by understanding how facets of mindfulness predict eating disorder symptoms over time. We examined whether facets of mindfulness predict eating disorder symptoms over time and vice versa. Individuals with an eating disorder diagnosis ( N = 124; 87.9% diagnosed with anorexia nervosa) and an undergraduate sample ( N = 290) completed measures of mindfulness at baseline. The clinical sample also completed these measures 1 month later. Individuals in the clinical sample had lower acting with awareness and higher observing than individuals in the undergraduate sample ( ps < 0.002). In the clinical sample, higher body dissatisfaction prospectively predicted lower acting with awareness ( p = 0.02). Lower acting with awareness prospectively predicted higher drive for thinness ( p < 0.01) and bulimic symptoms ( p < 0.01). Acting with awareness shows potential as a process that can be altered to effect positive outcomes on drive for thinness and bulimic symptoms.